Analisis Wacana Kritis Berita Utama di Surat Kabar "Pagar Alam Pos" Edisi November 2024 - Jesi Marsela; Henny Nopriani; Hikma Tansilo (Bastrando: Jurnal Bahasa dan Sastra Indonesia, 2025)
The purpose of this study is to describe the critical discourse of the headlines in the November 2024 Edition of the â€œPagar Alam Posâ€ newspaper. The data in this study are the critical discourse contained in the text of the letter in the November 2024 Edition of â€œPagar Alam Posâ€. The method used in this study is a qualitative method. Based on the November 2024 edition using the Critical Discourse Analysis approach of Teun A. Van Dijk's model, it can be concluded that local media plays an important role in shaping public discourse through the use of structured, systematic, and ideological language. This analysis involves three main dimensions, namely the text dimension (macrostructure, superstructure, and microstructure), the context dimension, and the social cognition dimension, which in total includes 97 analytical elements.